Job Satisfaction and Performance of the Secondary School Teachers in the Schools Division of Sulu, Philippines - A. Abdurahman, Norman (Journal of Multidisciplinary in Social Sciences, 2023)
This study’s objective was to determine the underlying factors that influence the secondary school teachers’ job satisfaction and performance in the Division of Sulu, Mindanao, Philippines. The respondents of the study included 139 secondary school teachers and 30 school administrators of the different secondary schools selected for the study. A structured questionnaire was used to gather the needed data. The statistical tools used were frequency counts and percentages, weighted mean, simple correlation, and multiple regression. The results of the study revealed that the administrators sometimes performed their duties as expected of them. The secondary school teachers were satisfied with their present pay; supervisors, and their colleagues were neutral with their safety and working conditions. The secondary school teachers were rated "Good" in the presentation of their lessons, expected student behavior, and wrap up. The teachers’ personal and professional characteristics did not significantly influence their performance. The administrators’ leadership behavior was significantly related to the job satisfaction of the teachers. There was a significant relationship between job satisfaction and performance of the secondary school teachers in the Division of Sulu, Philippines. In order to improve educational output specifically on teaching performance, secondary school teachers need to keep pace with the educational advancement through in-service training. The school administrators should maximize their efforts to improve teachers work and put measures in place to ensure the safety and security of the teachers.